TENTS guidelines : development of post-disaster psychosocial care guidelines through a Delphi process - Bisson, Jonathan I. (Array, 2010)
The article focuses on how best to plan and provide psychosocial care following disasters and presents the development of evidence-informed post-disaster psychosocial management guidelines. A three-round web-based Delphi process was conducted during which 106 experts rated the importance of statements generated from existing evidence using a one to nine scale. Participants reassessed their original scores in the light of others’ responses in the subsequent rounds. A total of 80 (72%) of 111 statements achieved consensus for inclusion. The statement ‘all responses should provide access to pharmacological assessment and management’ did not achieve consensus. The final guidelines recommend that every area has a multi-agency psychosocial care planning group, that responses provide general support, access to social, physical and psychological support and that specific mental health interventions are only provided if indicated by a comprehensive assessment. Trauma-focused cognitive–behavioural therapy (CBT) is recommended for acute stress disorder or acute post-traumatic stress disorder, with other treatments with an evidence base for chronic post-traumatic stress disorder being made available if trauma-focused CBT is not tolerated. The Delphi process allowed a consensus to be achieved in an area where there are limitations to the current evidence.